KAJIAN LITERATUR BIOSORBEN LIMBAH PERTANIAN DALAM MENGURANGI LIMBAH LOGAM PADA LINGKUNGAN - Kurniawan, Deni (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
Heavy metal pollution has become one of the most serious environmental problems today. The adsorption method is a relatively new process and has emerged as a potential alternative choice for removing heavy metals because it provides flexibility in design, the treated effluent is of high quality, is reversible and the adsorbent can be regenerated. This research aims to review articles that discuss several biosorbents from agricultural waste that are used to remove metal waste from the environment. The research uses the literature review method of several research results related to the literature on agricultural waste biosorbents in reducing metal waste in the environment. The research results show that agricultural waste from coconut shells, rice husks and corn husks is potential waste to be used as a biosorbent in the adsorption process because of its cheap price, abundant availability and sometimes pollutes the environment. Biosorbents from agricultural waste have good surface area and adsorption capacity in absorbing metal waste. The modification process for agricultural waste biosorbents is one of the processes that influences the morphology of the adsorbent and increases its adsorption capacity. Physical and chemical modification with thermal processes or the addition of acid and base compounds can increase the absorption efficiency of several adsorbents originating from agricultural waste.